Halftime rewarm-up with intermittent exercise improves the subsequent exercise performance of soccer referees - Yanaoka, T.; Yamagami, J.; Kidokoro, T.; Kashiwabara, K.; Miyashita, M. (The Journal of Strength and Conditioning Research, 2018)
This study investigated the effect of halftime rewarm-up (RW) with intermittent exercise on the subsequent exercise performance of soccer referees, determined by the Yo-Yo Intermittent Recovery Test level 1 (Yo-Yo IR1). Using a randomized cross-over design, 10 male referees were required to complete 2 trials. The trials consisted of the Loughborough Intermittent Shuttle Test, halftime, and Yo-Yo IR1 periods. During halftime, participants either rested on a chair (Control) or performed a halftime RW exercise for 15 minutes. The halftime RW protocol comprised 2.15 minutes of seated rest, followed by 2.15 minutes of running at 70% of the maximum heart rate (HRmax)—this cycle of recovery and running was repeated for a total of 13 minutes. The halftime RW protocol started at 1 minute after the commencement of the halftime period and concluded 1 minute before its end. The Yo-Yo IR1 performance, blood glucose, free fatty acids (FFAs), triglycerides (TGs), creatine kinase (CK), and lactate concentrations, the rating of perceived exertion, mean HR, and HRmax were analyzed. The Yo-Yo IR1 performance was higher in the halftime RW trial than in the control trial (3,095 ± 326 vs. 2,904 ± 421 m, P = 0.05). The mean HR and HRmax, blood glucose, FFA, TG, CK, and lactate concentrations did not differ between the trials. The rating of perceived exertion during the halftime RW, but not after the Yo-Yo IR1 period, was higher than that in the control trial. In conclusion, this study showed that halftime RW with intermittent exercise improves the subsequent exercise performance.